A glimpse at the intricate mosaic of ethnicities from Mesopotamia: Paternal lineages of the Northern Iraqi Arabs, Kurds, Syriacs, Turkmens and Yazidis - Dogan, Serkan; Gurkan, Cemal; Dogan, Mustafa; Balkaya, Hasan Emin; Tunc, Ramazan; Demirdov, Damla Kanliada; Ameen, Nihad Ahmed; Marjanovic, Damir (PLOS ONE, 2017)
Widely considered as one of the cradles of human civilization, Mesopotamia is largely situated in the Republic of Iraq, which is also the birthplace of the Sumerian, Akkadian, Assyrian and Babylonian civilizations. These lands were subsequently ruled by the Persians, Greeks, Romans, Arabs, Mongolians, Ottomans and finally British prior to the independence. As a direct consequence of this rich history, the contemporary Iraqi population comprises a true mosaic of different ethnicities, which includes Arabs, Kurds, Turkmens, Assyrians, and Yazidis among others. As such, the genetics of the contemporary Iraqi populations are of anthropological and forensic interest. In an effort to contribute to a better understanding of the genetic basis of this ethnic diversity, a total of 500 samples were collected from Northern Iraqi volunteers belonging to five major ethnic groups, namely: Arabs (n = 102), Kurds (n = 104), Turkmens (n = 102), Yazidis (n = 106) and Syriacs (n = 86). 17-loci Y-STR analyses were carried out using the AmpFlSTR Yfiler system, and subsequently in silico haplogroup assignments were made to gain insights from a molecular anthropology perspective. Systematic comparisons of the paternal lineages of these five Northern Iraqi ethnic groups, not only among themselves but also in the context of the larger genetic landscape of the Near East and beyond, were then made through the use of two different genetic distance metric measures and the associated data visualization methods. Taken together, results from the current study suggested the presence of intricate Y-chromosomal lineage patterns among the five ethic groups analyzed, wherein both interconnectivity and independent microvariation were observed in parallel, albeit in a differential manner. Notably, the novel Y-STR data on Turkmens, Syriacs and Yazidis from Northern Iraq constitute the first of its kind in the literature. Data presented herein is expected to contribute to further population and forensic investigations in Northern Iraq in particular and the Near East in general.